If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -8x = 11 Solving 5 + -8x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -8x = 11 + -5 Combine like terms: 5 + -5 = 0 0 + -8x = 11 + -5 -8x = 11 + -5 Combine like terms: 11 + -5 = 6 -8x = 6 Divide each side by '-8'. x = -0.75 Simplifying x = -0.75
| -56=-c-(-8) | | 4x+5=6.5 | | 3n^2+9n-12=0 | | 2(x+2)-5(2x+7)= | | 7x+2=-103 | | 2x+10-3=-2x+1 | | 10-2*x=4 | | -.75+j=-3.5 | | 4x+126=11x | | 19-2*x=4 | | 96=-24c | | -6a-5b-4= | | -3.75+j=-3.5 | | 96=-24 | | 4-3*x=34 | | 2x+7y+8= | | (v-3)(2v+1)= | | 6a-5b-4= | | 2-6*x=5 | | z^3-3z^2+(1+3i)z-6i+a=0 | | 2a^2-ab-15b^2=0 | | .5*x+1=11 | | c=15+40 | | 4x+10=x+37 | | -4+2t=1 | | 58=3a+10 | | 5-2*x=19 | | 8y+23=33 | | 3x+1=-7-5x | | 533.71=40y+2.5y | | y=40y+2.5y | | 2y-2x+6=0 |